(untitled) (UNIZIK Journal of Educational Management and Policy, 2025)
Artificial intelligence (AI) is rapidly transforming various sectors, and education is no exception. This article explores the application of AI in educational management, examining its uses, the evolving roles of educational managers, and the management of AI implementation. By analyzing recent studies and frameworks, this paper underscores the potential benefits and challenges associated with integrating AI technologies into educational environments. AI offers significant potential for streamlining administrative tasks, enhancing decision-making, and personalizing educational experiences. However, it also presents challenges related to ethical considerations, data privacy, and the need for new management approaches. This article discusses these opportunities and challenges, providing insights and recommendations for effective AI integration in educational settings.